Assessing the phytoplankton and water quality of Kingston Harbour and Hellshire coast, Jamaica, after the implementation of a waste water treatment facility - Liu, Helen A.; Broomfield, Sheree A.; Duncan, Anya F.; Grant, Leon O.; Francis, Patrice A.; Webber, Dale F.; Webber, Mona K. (Revista de Biología Tropical, 2014)
Deteriorating water quality of Kingston Harbour, due primarily to sewage discharge and its effect on nearby Hellshire Coast, has been an issue since the 1970s. The implementation of a new sewage treatment facility in 2007 to receive the harbour’s waste at Soapberry was expected to make a positive difference. Physico-chemical and biological parameters were used to assess water quality to determine the effect of the facility. Eleven stations used in earlier studies (1990 to 1998) were re-sampled to represent Kingston, Hunts Bay and North East Hellshire coastline over a four week sampling regime between May and June 2011. While temperature, salinity, turbidity, dissolved oxygen and pH remained unchanged between the 1990’s and 2011, BOD5, faecal coliform and nitrate concentrations indicated that the water quality had improved minimally in Kinsgton and Hellshire,and deteriorated significantly in Hunts. Phytoplankton biomass decreased in Kingston (from 3.84 mg m-3 in 1998 to 2.81 mg m-3 in 2011) and increased significantly in Hunts (from 14.69 mg m-3 in 1998 to 24.17 mg m-3in 2011). Biomass along Hellshire was similar (2.15 mg m-3 in 1998; 2.45 mg m-3 in 2011). In 1998 the nanoplankton biomass (2.7 to 20μm) dominated throughout the Harbour. In 2011 Hunts Bay was dominated by net-plankton (>20μm), indicative of eutrophic waters. Rev. Biol. Trop. 62 (Suppl. 3): 241-248. Epub 2014 September 01.